The effectiveness of the fundamental right to health in the light of proportionality and the theory of the possible reserve - Fleury, João Felipe da Silva (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2021)
The present work aims to outline an analysis about the realization of the fundamental right to health in consideration with the principle of proportionality and the theory of reserve of the possible. The objective is to analyze the fundamental right to health as a limited right that depends on the allocation of equally limited financial resources by the State. The study is justified by the discussions under the doctrinal and practical focus on the national scene. Thus, the bases of the fundamental right to health are approached, in a summarized manner, as well as the limitation of financial performance by the federated entity, from the perspective of the possible reserve. The research was developed through a dogmatic and socio-legal approach, using bibliographic and documentary analyzes as research techniques.